The translator : a novel - Schuyler, Nina, 1963- (New York : Pegasus Books, 2013)
When an accident leaves translator Hanne Schubert without the ability to speak her native language, she heads to Japan to fight demons from her past and her present after a Japanese novelist accuses her of sabotaging his work.
Keywords: Women translators -- Fiction; Novelists, Japanese -- Fiction; Mothers and daughters -- Fiction; Translating and interpreting -- Fiction; Japanese novelists -- Fiction; Mother-daughter relationship -- Fiction; Japan -- Fiction; Japan -- Fiction